Neonatal Cholestasis as Initial Presentation of Portosystemic Shunt: A Case Report - DOĞAN, GÜZİDE; Dogan, Güzide; Duzgun, Fatih; Tarhan, Serdar; Appak, Yeliz Cagan; Kasrga, Erhun (My University, 2016)
Congenital intrahepatic portosystemic shunts are rare in children. Portosystemic venous malformations are characterized by extreme clinical variability. We report a full-term 33-day-old male infant presenting with neonatal jaundice. On physical examination, he had generalized icterus and the liver was palpable 3.5 cm below the right costal margin. He had no other symptoms. Laboratory tests showed AST 632 U/L, ALT 198 U/L, total bilirubin 12.1 mg/dL, conjugated bilirubin 10.2 mg/dL, alkaline phosphatase 753 U/L, GGT 47 U/L and glucose 67 U/L. Colour Doppler ultrasonography showed the left portal vein was more dilated than the right portal branch and communication with dilated left hepatic vein. There was no evidence of portal hypertension, heart failure, hepatopulmonary syndrome and encephalopathy during his hospital stay, so he was discharged from the pediatric department and his parents advised to attend monthly follow-up. Congenital portosystemic shunts are rarely observed in the childhood period. 1 Depending on anatomic characteristics they may be intrahepatic or extrahepatic. 2 Intrahepatic portosystemic shunts (PSS) are observed between the portal vein and hepatic vein or vena cava inferior. 3,4 Small shunts may close themselves before the age of 2 years. 5 With the increase in use of imaging methods, diagnosing PSS has become easier, with an increase in the number of cases reported. 6 Neonatal cholestatis is a frequent complication of PSS. 1 We present a case presenting with neonatal cholestasis diagnosed with congenital intrahepatic PSS.